Aid and terrorism: a dynamic contracts approach with interlinked moral hazard. Issue 2 (29th October 2019) - Roy, Jaideep; Chowdhury, Prabal Roy
Abstract : Purpose: In a global environment where terrorist organisations based in a poor country target a rich nation, this paper aims to study the properties of a dynamically incentive compatible contract designed by the target nation that involves joint counter-terror tasks with costly participation by each country. The counter-terror operations are however subject to ex post moral hazard, so that to incentivise counter-terror, the rich country supplies developmental aid. Development aid also helps avoid unrest arising from counter-terror activities in the target nation. However, aid itself can be diverted to non-developmental projects, generating a novel interlinked moral hazard problem spanning both tasks and rewards. Design/methodology/approach: The authors use a dynamic model where the aid giving countries and aid receiving countries behave strategically. Then they solve for the sub game perfect Nash equilibrium of this game. Findings: The authors characterise the optimal contract, showing that the dynamic structure of counter-terror resembles the shock-and-awe discussed by military strategists. The authors then prove that it is not necessarily the case that a more hawkish (resp. altruistic) donor is less pro-development (resp. softer on terror). In addition, the authors show that it may be easier to contract for higher counter-terror inputs when the recipient is more sympathetic to terrorists. The authors also discuss other problems faced by developing nations where this model can be readily adopted and the results can endorse appealing policy implications. Originality/value: The authors characterise the optimal contract, showing that the dynamic structure of counter-terror resembles the shock-and-awe discussed by military strategists. It is proved that it is not necessarily the case that a more hawkish (resp. altruistic) donor is less pro-development (resp. softer on terror). In addition, the authors show that it may be easier to contract for higher counter-terror inputs when the recipient is more sympathetic to terrorists. Other problems faced by developing nations are also discussed where this model can be readily adopted, and the results can endorse appealing policy implications. These results have important policy implications, in particular in today's world.